Islamic Fintech and Digital Banking Adoption: A Systematic Review of Established Models of Fintech Adoption and Their Influence on Sharia Financial Inclusion and Performance - Sari, Nurma (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2025)
Islamic fintech and digital banking have become important catalysts in realising shariah-compliant financial inclusion. This study aims to systematically synthesise the use of technology behaviour theories - namely Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), and Theory of Planned Behaviour (TPB) in explaining the adoption of Islamic fintech services and its influence on financial inclusion and financial performance of Muslim individuals or businesses. Using the Systematic Literature Review (SLR) approach based on PRISMA 2020 protocol, 568 articles were identified from Google Scholar (spanning 2020-2025). After screening and eligibility assessment, 20 verified articles were included in the thematic synthesis. Results show that perceived usefulness, trust, and religiosity are the dominant determinants in TAM and TPB models, while performance expectancy and facilitating conditions appear mostly in UTAUT. Financial inclusion is a significant mediating variable in bridging the relationship between adoption intention and improved financial performance, especially in the MSME sector. This study also identified important gaps, such as the limited number of longitudinal studies, the lack of integration of maqashid sharia as an outcome indicator, and the absence of a cross-theoretical synthesis model that considers spiritual-financial alignment. This study recommends the development of a framework to integrate